Functional characterization of long non-coding RNAs in Schistosoma mansoni - Silveira, Gilbert de Oliveira (2022)
Schistosomiasis is an important parasitic disease with a high impact on morbidity and mortality rates, affecting more than 230 million people in 76 countries. Schistosoma mansoni is the most prevalent species in Africa and Latin America, presenting a complex life cycle with six different stages: eggs, miracidia, sporocysts, cercariae, schistosomula, adult males and adult females (sexual dimorphism). Understanding schistosome biology at the molecular level may suggest new therapeutic alternatives. Long non-protein-coding RNAs (lncRNAs) are RNAs of more than 200 nucleotides with low or no protein-coding potential that, in humans and many other species, can act as regulators of protein-coding gene expression, stem-cell maintenance and drug resistance. Due to their tissue-specific expression and multifaceted functions, lncRNAs have been proposed as new therapeutic targets in human diseases. In this Thesis, we produced a literature review of the works that identified lncRNAs in protozoa, Schistosoma and other helminths, and we demonstrated for the first time the impacts on S. mansoni physiology caused by the in vitro silencing of an intergenic lncRNA (Introduction). We then determined the appropriate reference genes for normalizing RT-qPCR data from samples from the six different developmental stages of S. mansoni (Chapter 1). Further, we showed by re-analyses of public RNA-Seq data from female parasites treated with 5-Aza-Cytidine (an epigenetic drug that inhibits female oviposition and ovarian development), that hundreds of lncRNAs were differentially expressed between control and treated conditions. Many lncRNAs belonged to metabolism-related co-expression modules in males, and some were validated by RT-qPCR (Chapter 2). Subsequently, by reanalyzing public data from single-cell RNA-Seq (scRNA-seq) from adult S. mansoni, we characterized the expression profile of lncRNAs in the 68 identified cell clusters. The cell clusters that contained the most lncRNA markers were male and female gametes and tegument progenitor cells. We identified neural cell-specific marker lncRNAs. By whole mount in situ hybridization, with single or double labeling, we localized the specific expression of 13 of the 16 selected marker lncRNAs (Chapter 3). Finally, re-analysis of public RNA-Seq data from adult worms, recovered from hamsters infected with single-sex or dual-sex cercariae, identified thousands of differentially expressed lncRNAs. We selected twelve lncRNAs and validated their expression levels in a model of in vitro cultures of paired or unpaired parasites that is similar to what performed before. in vitro and in vivo silencing of four of the selected lncRNAs showed that they play key roles in cell proliferation in adult worms and their gonads and are essential for female vitellaria maintenance, adult worm reproduction and egg development. in situ hybridization has shown that these four lncRNAs are expressed in tissues that correlate with the phenotypes observed in the in vitro silencing (Chapter 4). Overall, these results show that lncRNAs are essential components of S. mansoni biology, presenting significant potential as new candidates for therapeutic targets.